Sexual Deviations of Prisoners in Conditions of Isolation - DZHANSARAYEVA, Rima Yerenatovna; BAISALOV, Ali Dzhumamuratovich; MALIKOVA, Sholpan Baltabekovna; ATAKHANOVA, Gulzagira Makhatovna; YELNUR, Yerenat (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
In conditions of isolation there is consistent implementation of the methods for improving material and welfare support of prisoners, correction of their disciplinary programs adjusted for current realia, improvement of security and control over them, optimization of arrangement and tactics of field investigation activities and special prevention activities in order to reveal and prevent offending behavior in penitentiary facilities. These measures in whole are important for law enforcement in the places of confinement and security protection of prisoners and officers of penitentiary facilities. However, failures in the activities of different organization elements of a penitentiary facility cause deviant behavior of prisoners, which may manifest in commitment of penitentiary crimes and offenses. Deviant sexual behavior of prisoners in penitentiary facilities undermines correctional process, negates effectiveness of preventive measures in a penitentiary facility, and impedes proper organization of execution and service of sentence, being a background element of penitentiary crimes, often leads to conflict situations between the prisoners, which they usually solve by abusive actions. As the basis of deviant sexual behavior of prisoners is their personal defects, thus applied disciplinary measures don’t have a significant influence on them. The knowledge of peculiarities of criminal world and the norms of prisoners’ behavior allows a penitentiary facility’s administration to objectively analyze the crime situation in the institution as well as to control and forecast it in a proper and timely way.